Factors that influence individual utilisation of internet payment systems - Mohamad Amin, Muhamad Sade (2018)
The overall number of Internet payment users in Malaysia has increased but the Malaysian consumers response towards the Internet payment systems falls short of expectations. The main objective of this thesis is to expand a theoretical model that establishes how intentions towards the utilisation of Internet payment system are designed and to what extent they are related to the actual use of Internet payment systems. The thesis also examines the role of customer trust in Internet payment acceptance and the perceptual dissimilarities among users on the foundation of their demographic characteristics of generational differences and gender. The thesis incorporates variables related to behavioural and environmental uncertainty (trust and perceived risk), technology acceptance constructs (perceived usefulness, ease of use, facilitating condition and social influence), and users’ personal charateristics (generational differences and gender) into a comprehensible and parsimonious model. The Analysis of Moment Structures for Structural Equation Modelling (AMOS-SME) technique is used to meticulously test the validation of measurement models and to analyse the massive set of interrelationship between these variables and their comparative consequences on user intention and actual use of Internet payment systems. The data used in this study are gathered from 308 respondents through questionnaire survey of the Internet payment system among Malaysian bank consumers .The research finds that performance expectancy, effort expectancy and social influence have significantly influenced the usage of Internet payment systems in Malaysia.